Innovating Educators Online - The, Star (The Star, 2019)
Think back to the first classroom you ever entered, be it a school or a nursery. Chances are there was a blackboard with coloured chalk where you focused most of your attention. You were probably working from a booklet or on paper using pencil and crayons and drawing pictures by hand.